Developing high-performance enzymatic biofuel cell - Yan, Ruyu (2013)
Nowadays, biomaterials is becoming a promising green and renewable technology compared with conventional fossil fuels. It occurs either in forms of biofuels, which is a process of converting chemical energy in the substances into mechanical energies, or biofuel cells (BFCs), which use enzymes as the catalysts to harvest energy from environmental and sustainable fuels abundantly producible from biological systems.